Implementation of Legal Protection for Economic Exploitation of Children - Kahnovich, Yan; Rezki, Annissa (Universitas Muhammadiyah Palembang, 2022)
Numerous parents utilize or even manipulate their children for their own profit. Typically, their treatment is motivated by money or economic issues. Numerous individuals immerse themselves in the demands of their existence without thinking about what they require and require. In this study, a qualitative descriptive methodology was employed. Based on the findings of this study, it was determined that there was a legal void in the implementation of criminal acts against offenders of economic exploitation of children. Even though the child's status in the eyes of the law has been accorded special protection, as stipulated in Law No. 23 of 2002 on Child Protection, this protection is not absolute. Children entitled to parental protection, affection, and supervision are educated and cared for in accordance with their rights as children so that there are no growth phase deviations. As an institution that concentrates on incidents of violence against children, the National Human Rights Commission can also demonstrate that numerous acts of violence have been committed against Indonesian children.